Approach to the Landscape of Bacterial Diseases in Wayuu Communities, Colombia: Acute Diarrheal Disease and Febrile Bacterial Syndromes - Paula Lucía Díaz-Guevara; Zonia Alarcón; Nancy Yaneth Flórez-Delgado; Lucy Angeline Montaño; Laura Gómez; Vanessa Melo; Diego Prada; Daniel Velandia-Rodriguez; Gloria Mercedes Puerto-Castro; Patricia Escandón; Jaime Moreno (The American Journal of Tropical Medicine and Hygiene, 2026)
ABSTRACT. Indigenous communities face a disproportionate burden of neglected communicable diseases, particularly acute diarrheal disease (ADD) and bacterial febrile illness (BFI), in contexts with limited access to diagnosis and medical care. The circulation of bacteria associated with ADD and BFI was evaluated in Wayuu indigenous communities of northern Colombia. Four health brigades were conducted in 14 Wayuu communities, with 86 ADD samples, 210 BFI blood samples, and 237 BFI serum samples for BFI collected according to clinical symptoms. The samples were analyzed using conventional bacteriology, real-time polymerase chain reaction tests, serological tests, and whole-genome sequencing for the recovered isolates. In ADD, a bacterial agent was isolated in 17.4% of the fecal samples. Salmonella enterica w as the predominant enteropathogen (12.8%), with four identified serovars. The serovars Salmonella Poona (0 single-nucleotide polymorphisms [SNPs]) and Salmonella Uganda (0–2 SNPs) were closely related, suggesting clonal patterns compatible with independent outbreak events within the community. Escherichia coli O157:H7-, Vibrio cholerae non-O1/non-O139, and Listeria kieliensi s were also detected. Genomic analyses did not reveal determinants of highly invasive or multidrug-resistant strains, although plasmids with horizontal transfer potential were detected. In BFI, the seroprevalence was 3.4% for Brucella spp., 6.8% for Leptospira spp., and 14.2% for Rickettsia rickettsii , revealing exposure to bacterial zoonoses. The Wayuu community exhibits circulation of bacteria associated with both ADD and BFI, including underdiagnosed zoonotic pathogens. These findings highlight the need to strengthen integrated surveillance and One Health approach strategies, involving the active participation of vulnerable indigenous populations.